Biology of Legumes and their Importance - Ma’muraxon, Atabayeva; qizi, Mukhtoraliyeva Mukhlisa Dilshod (American Journal of Biology and Natural Sciences, 2024)
Legumes belong to the Fabaceae family, which includes mung beans, soybeans, beans, peas, lentils, green peas, vetch, fenugreek, common peas, and lupins. More than 60 species of legumes belonging to 17 genera are known worldwide.